Peran Zakat Melalui Program Ekonomi dan Pendidikan Terhadap Tingkat Kesejahteraan Mustahik di Banjarmasin - Indah Permata Sari; Sri Maulida (Universitas Ahmad Dahlan, 2023)
The main problem in this study is how the role of zakat in economic and educational programs distributed by the South Kalimantan Baznas in the welfare of the mustahik in the city of Banjarmasin. The purpose of this study was to determine the role of zakat in economic and educational programs distributed by the South Kalimantan Baznas in the welfare of the mustahik in the city of Banjarmasin. The type of research used is descriptive qualitative research with field research. The data analysis technique went through three stages, namely data reduction, data presentation, and drawing conclusions. The results in the field show that changing the zakat orientation such as productive orientation is proven to be able to gradually and sustainably improve the community's economy by sticking to sharia rules, and mustahik still feel helped by the existence of the education zakat which is where they should bear all educational needs, all of this will have a positive effect on socio-economic stability and education in Indonesia.